Competence of Islamic Religious Education Teachers from The Perspective of the Quran - Suharsongko, M. Edi; Munawiroh, Munawiroh; Suharwanto, Suharwanto (Riviera Publishing, 2023)
This study aims to obtain a map of the pedagogic, professional, and personality competencies of Islamic religious education teachers from the perspective of the Koran in the city of South Tangerang and their development strategy. This type of research is library and field research using a qualitative descriptive research design. The methodology used in this study is a mixed-method research approach. The object of this research is the teacher of Islamic religious education in South Tangerang. The research data were obtained through questionnaires, observation, interviews, and documentation techniques. Data were analyzed using an interactive data analysis model carried out descriptively. Based on the results of the study shows that the personality competence of Islamic religious education teachers in South Tangerang City on several achievement indicators shows a low level of competence, including; lack of innovation in learning, lack of activating students, lack of self-development, lack of discipline in assignments, not completing assignments thoroughly and improving the quality of personality competence of Islamic religious education teachers, including coaching Islamic religious education teachers, fostering Islamic religious education curricula at the kindergarten, junior high, and high school/vocational school levels, collaboration with the South Tangerang city government in developing Islamic religious education, conducting studies, research and mock studies, holding competitions for students and teachers.